(untitled) (Scientific journal of the Fergana State University, 2023)
This article gives an idea of the lexical and phraseological features of the official style of work and the use of phrases and words used in chancery. In addition, the article sufficiently covers the vocabulary and phrases of official correspondence and diplomatic substyle.